Damage imaging in composites using nonlinear vibro‐acoustic wave modulations. Issue 2 (16th July 2017) - Pieczonka, L.; Zietek, L.; Klepka, A.; Staszewski, W.J.; Aymerich, F.; Uhl, T.
Abstract: The paper deals with the application of nonlinear vibro‐acoustic modulation technique for detection and localization of impact damage in a laminated composite plate. An imaging procedure—based on the nonlinear vibro‐acoustic modulation sidebands—is proposed. The procedure relies on simultaneous low‐frequency modal and high‐frequency ultrasonic excitations. Laser scanning vibrometry is used to analyze the amplitude of modulation sidebands in vibro‐acoustic responses. This analysis is performed for different positions on monitored structure to reveal the location and shape of damage. The method is illustrated using a simple example of impact damage detection in a composite plate. The experimental damage detection results are compared with the results obtained from the previously used approach on the basis of higher harmonic generation. The proposed method demonstrates better ability to locate damage in these comparative tests without the need to increase the measurement bandwidth to the higher harmonics regime. The work shows that the local defect resonance analysis can improve damage detection results of both compared approaches.